Alternative feed for next generation aquaculture and poultry systems in the Global South: a preliminary assessment of the nutritional composition of human manure-derived feed - Nartey, Eric Gbenatey; Alegbeleye, Oluwadara; Ayertey, Desmond; Amponsah, Andoh; Dossou, S. (International Water Management Institute, 2025)
Aquaculture and poultry farming are expanding rapidly in the Global South but rising feed costs—mainly due to expensive fish feed and shortages of cereals—threaten profitability. To cut costs, some Asian farmers use nutrient-rich wastewater for fish cultivation, although health risks underline the need for safer solutions. The International Water Management Institute (IWMI) has developed human manure-derived pellets that are certified pathogen-free and are attracting interest as an alternative animal feed. This technical note compares the nutritional composition of the pellets with the conventional feed requirements for fish and poultry. The results show that the pellets provide essential macro- and microelements, but the levels of carbohydrates, proteins, and lipids are lower than those required for both fish and poultry. While the pellets meet Ghana's poultry feed standards for protein and lipids, their crude fiber content is at the maximum for both fish and poultry in sub-Saharan Africa and Asia. The low lipid content is beneficial as it potentially reduces fat buildup in animals. However, to serve as a complete feed, these pellets need additional supplementation, especially in terms of protein, carbohydrates, and certain vitamins.